Sinergi Project Based Learning dan Pembelajaran Bermakna untuk Meningkatkan Hasil Belajar Matematika - Nuning Setyowati; Mawardi Mawardi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2018)
Mathematics was a lesson that must be published in all levels of education. So, the competence of mathematics should be understood by students. However, there were some problems on student’s mathematics learning outcomes at the first semester in 4th grade of SDN Gendongan 02. There were 39 students, but only 46% (18 students) got score above minimum completeness criteria (KKM). While 54% (21 students) got score under the KKM. The aims of this reseacrh was to increased the mathematics learning outcomes through the synergy of project based learning and meaningful learning. The type of this research was action research by using stringer model. This research held in two cycles with three stages. The stages consist of look, think, and act. The data collection used some instruments such as test, observation sheets, and field notes. The technique of data analysis used comparative descriptive technique. The subjects of the research were students in 4th grade of SDN Gendongan 02. The result of completeness mathematics learning outcome in the first cycle was 72,5% and in the second cycle was 80%. Student’s mathematics learning outcomes in the second cycle were better than the mathematics learning outcomes in the first cycle. Based on the result, the synergy of project based learning and meaningful learning can increase mathematics learning outcomes. Therefore, the synergy of project based learning and meaningful learning were suggested to be applied at mathematics.